PENGARUH PENGGUNAAN AIR VENT TUBE TURBULANCE (AVTT) TERHADAP KINERJA MESIN MOTOR MATIK 4 LANGKAH - Komarudin Komarudin; Primson Yohanes (Bina Teknika, 2016)
Automatic motor engine 4 stroke system uses a carburetor engine is still less than optimal performance. To overcome these problems it created tools that the air intake tube Turbulent Air Vent Tube (AVTT). AVTT is a tool that serves to improve the quality of air intake into the cylinder motor fuel, by changing the air flow laminar to turbulent flow so that the fuel combustion process is ideal close to perfect. AVTT tube designed using aluminum material types AVTT in 6069. Installation of the air filter duct size is adjusted to the motor air filter diameter hole. To determine the performance of a motorcycle engine can be made by automatic test engine performance using a dynamometer. Tests conducted to analyze the effect of the use of AVTT on engine performance includes the automatic motor torque, data, air fuel ratio and fuel consumption. The test results showed that the use AVTT able to increase the torque of 0.06 - 13.74%, power from 0.08 - 13.74%, and the air fuel ratio of 18: 1 - 10: 1, and can reduce fuel consumption 2 - 9 % in both engine variants automatic motor 4 stroke.